2001
DOI: 10.1017/s0266462301107099
|View full text |Cite
|
Sign up to set email alerts
|

Panelists' Views of 68 Nih Consensus Conference

Abstract: Objectives: To analyze the response patterns and trends of 68 surveys of successive NIH consensus panels' views on the NIH consensus process.Methods: Each panel's responses were compared to an “average” panel's responses calculated by determining the mean response for each survey question across panels.Results: The results show a stable pattern of panelists' generally positive views. However, several conferences were judged very positively and some very negatively compared to the norm. Most negatively viewed c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 2 publications
0
7
0
1
Order By: Relevance
“…The poor effectiveness of the conference in this respect is striking, considering that the desired outcome was merely a change in nomenclature rather than an alteration in clinical management, as was the case in many of the other NIH consensus conferences cited above. This lack of effectiveness is particularly notable, given that a recent study found that this particular NIH Consensus Conference received extremely positive reviews from the panel in virtually all conference characteristics, coming in second out of 68 conferences studied in overall conference quality, fourth in panel cohesiveness, and fifth in evidence quality 18 . However, an external assessment of the performance of the Conference is not available.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…The poor effectiveness of the conference in this respect is striking, considering that the desired outcome was merely a change in nomenclature rather than an alteration in clinical management, as was the case in many of the other NIH consensus conferences cited above. This lack of effectiveness is particularly notable, given that a recent study found that this particular NIH Consensus Conference received extremely positive reviews from the panel in virtually all conference characteristics, coming in second out of 68 conferences studied in overall conference quality, fourth in panel cohesiveness, and fifth in evidence quality 18 . However, an external assessment of the performance of the Conference is not available.…”
Section: Discussionmentioning
confidence: 98%
“…This lack of effectiveness is particularly notable, given that a recent study found that this particular NIH Consensus Conference received extremely positive reviews from the panel in virtually all conference characteristics, coming in second out of 68 conferences studied in overall conference quality, fourth in panel cohesiveness, and fifth in evidence quality. 18 However, an external assessment of the performance of the Conference is not available. A limitation of the Consensus Conference format is its sometimes adversarial nature and the lack of peer review of the material presented.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In general, studies comparing various consensus development methods have not clearly shown a preferred method; a single collection of comparative studies normally shows all possible outcomes: better than, worse than, or equivalent 2,3 . The consensus development conference as formulated by the NIH is viewed favorably on the whole as a process by both users of the consensus statements and by the panelists who participate 4 …”
Section: Nih Consensus Development Conference Relevant To Transfusionmentioning
confidence: 99%